Exploring The Relationship Between Emotional Intelligence And Organizational Citizenship Behavior, And The Potential Moderator Effect Of Job Control In Service Companies - Mohamed Eljadi, Ahmed (Universiti Sains Malaysia, 2007)
The present study was designed to examine the relationship between emotional intelligence's dimensions of employees working 1n service companies located in Penang and their organizational citizenship behaviors as perceived by their current supervisors in organization and to examine whether job control moderates the relationship between emotional intelligence's dimensions and organizational citizenship behavior's dimensions. Hypotheses were tested with 104 respondents received frmn 2 organizations.